Genome-wide association study of resistance to Mal de Río Cuarto disease in maize - Rossi, Ezequiel Alejandro (2020)
Argentine maize has been extensively screened for incidence (INC) and severity (SEV) of Mal de Río Cuarto disease (MRC), caused by Mal de Río Cuarto virus (MRCV), family Reoviridae, genus Fijivirus, narrowing the breeding genetic basis. Both traits are highly heritable phenotypic measurements, and quantify the strong disease impact on grain yield. The adaptation of exotic germplasm to variation of those traits has not been explored. The aim of this work was to identify, in a non-local and diverse panel of maize inbred lines, novel genomic regions associated with resistance to MRC. First, we phenotyped 206 maize inbred lines from the International Maize and Wheat Improvement Center (CIMMYT), in several environments of the MRC-endemic area under natural virus infection, to obtain the best linear unbiased predictor (BLUP) of line effects regarding INC and SEV. A multi-environment and multi-trait mixed linear model was fitted to derive the multivariate BLUPs. Genetic variance and mean-basis heritability were high in both traits and a significant genetic correlation among them was found. Second, we performed a genome-wide association study (GWAS) by linking the BLUPs with 78,376 SNP markers available for 186 lines. The GWAS identified new alleles for resistance to MRC in six genomic regions from the exotic germoplasm. Four of them reduce symultaneously the appearance and severity of disease symptoms. Improved susceptible parental lines through marker-assisted recurrent selection would allow us to increase the resistance of maize hybrids to MRC disease.